Reduction of Fusarium head blight and trichothecene contamination in transgenic wheat expressing Fusarium graminearum trichothecene 3-O-acetyltransferase - Yulfo-Soto, Gabdiel; McCormick, Susan; Chen, Hui; Bai, Guihua; Trick, Harold N.; Hao, Guixia (Frontiers in Plant Science, 2024)
Fusarium graminearum, the causal agent of Fusarium head blight (FHB), produces various mycotoxins that contaminate wheat grains and cause profound health problems in humans and animals. Deoxynivalenol (DON) is the most common trichothecene found in contaminated grains. Our previous study showed that Arabidopsis expressing F. graminearum trichothecene 3-O-acetyltransferase (FgTRI101) converted DON to 3-acetyldeoxynivalenol (3-ADON) and excreted it outside of Arabidopsis cells. To determine if wheat can convert and excrete 3-ADON and reduce FHB and DON contamination, FgTRI101 was cloned and introduced into wheat cv Bobwhite. Four independent transgenic lines containing FgTRI101 were identified. Gene expression studies showed that FgTRI101 was highly expressed in wheat leaf and spike tissues in the transgenic line FgTri101-1606. The seedlings of two FgTri101 transgenic wheat lines (FgTri101-1606 and 1651) grew significantly longer roots than the controls on media containing 5 µg/mL DON, however, the 3-ADON conversion and excretion was detected inconsistently in the seedlings of FgTri101-1606. Further analyses did not detect 3-ADON or other possible DON related products in FgTri101-1606 seedlings after adding deuterium-labelled DON into the growth media. FgTri101 transgenic wheat plants showed significantly enhanced FHB resistance and lower DON content after they were infected with F. graminearum, but 3-ADON was not detected. Our study suggests that it is promising to utilize FgTRI101, a gene that the fungus uses for self-protection, for managing FHB and mycotoxin in wheat production.